Community perceptions of the social and economic impacts of COVID-19 in Myanmar: Insights from the second round of the National COVID-19 Community Survey (NCCS) - July/August 2020 - Oo, Than Zaw; Lambrecht, Isabel B.; Headey, Derek D.; Goudet, Sophie (International Food Policy Research Institute, 2020)
To better understand the economic and social impacts of the COVID-19 crisis on Myanmar’s diverse rural and urban communities, a large-scale community telephone survey was conducted. The first survey round was implemented in June and July 2020 with respondents from 308 different communities covering 168 of Myanmar’s 356 townships. A second survey round was conducted in July and August 2020 with respondents from the same communities and from communities in an additional 185 townships. We report key findings from this second round, comparing to those from the first round.